Dietary intake and nutritional risk in Mediterranean adolescents in relation to the severity of the eating disorder. Issue 8 (25th September 2014) - Aparicio, Estefania; Canals, Josefa; Pérez, Susana; Arija, Victoria
Abstract: Objective: To assess the relationship between the degree of severity of eating disorders (ED) and energy and nutrient intakes and nutritional risk in a mixed-sex adolescent population without clinical symptoms. Design: Cross-sectional study. Setting: Data were collected in schools. Subjects: Adolescents ( n 495) aged 14·2 (sd 1·0) years. The Eating Attitudes Test was used to detect adolescents at risk of ED (rED) and a structured interview based on the criteria of the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, was used to diagnose eating disorder not otherwise specified (EDNOS). Dietary intake was quantified using the 24 h recall method over three days and the probability of inadequate intake was determined. Results: Females presented lower intakes of energy, macronutrients and micronutrients (Ca, Fe, Mg, K, P, Na, thiamin, vitamins E, C, B6, B12, pantothenic acid, folic acid) because the severity of their ED was greater. These lower dietary intakes led to nutritional risk (for Ca, Fe, Mg, P, vitamins A, D, B6 ) in more than 80 % and 60 % of females with EDNOS and rED, respectively. The multiple linear regression models showed that the rED and EDNOS groups presented a lower energy intake of 1597·4 kJ/d (381·8 kcal/d) and 3153·0 kJ/d (753·6 kcal/d), respectively. In contrast, little difference was observed in the nutritional intakes of males. Conclusions: The female adolescents showed lower energy and nutrient intakes as the ED became more severe, which led to energy, vitamin and mineral deficiencies in a high percentage of females with ED. These nutritional risks could hinder adequate physical and psychological development and lead to chronic ED.